jazzing philosophy with children. an improvising way for a new pedagogy. - santi, marina (2017)
This paper is based on the content of the talk held at the ICPIC Conference in Madrid, titled “Improvising as a way of inquiring and inventing” in which the jazz metaphoe for education and philosophy is introduce. The arguments proposed are adapted to respond also to some critical issues put forward by Gert Biesta in his paper about philosophical work with children and the related experience in schools through Philosophy for/with Children programmes.  My contribution to the discussion deals with two main foci. The first one is theoretical and considers improvisation as expression of human cognitive constructivism and form of adaptive/exaptive human agency in the environment. Improvisation is interpreted as a privileged form of “complex thinking”, in which the three components identified by Lipman - critical, creative and caring thinking - are integrated and mutually implemented. The second focus is pragmatic and proposes eight “jazz” doors to embody education in the dimension of improvisation, opening teaching to the authentic experience of changing implied in growing/aging, in which the stability of identities are always at risk. A jazzing way to Philosophy for/with Children is proposed as antydote to the risk of learnification of education and capitalization of human skills to which – according to Biesta – Philosophy for/with Children seems to be exposed in its school application, while proposing a jazz framework for a new “poor pedagogy”.